ANALISIS PREFERENSI KONSUMEN PRODUK TEH CELUP - Nurul Atikah (2020)
This research under study is a quantitative descriptive research with the aim to find out and prove the brand, packaging, price and taste variables influence partially consumers' preferences for tea bags. The population taken in this study is the consumers of tea bags in the North Jakarta area. Samples taken as many as 100 respondents using probability sampling method by distributing questionnaires through Google form to respondents. The data analysis technique used is descriptive analysis and inferential analysis using the analysis tool, namely Partial Least Square (PLS). The results of this study indicate that brand variables have no effect on consumer preferences with a path coefficient of 0.059, packaging variables have a significant effect on consumer preferences with a path coefficient of 0.560, price variables have a significant effect on consumer preferences with a path coefficient of 0.370, and taste variables no effect on consumer preferences with a path coefficient of 0.007.